Demographic Ageing in Romania’s Rural Area - Daniela Violeta Nancu; Liliana Guran-Nica; Mihaela Persu (Human Geographies: Journal of Studies and Research in Human Geography, 2010)
Europe has faced for several decades and is still facing an ageing process of its population. Within it, Romania, a country, striving to successfully integrate into the European Union, is also experiencing the same process. The ageing process of the Romanian population started at the beginning of the 20th century and evolved progressively, ever since, with significant visible rates in the rural areas. Romania’s population age structure, at the beginning of the Third Millennium, was, according to international experts, not significantly aged compared to populations of the economically advanced countries of Europe. Due to falling birth-rates and the labor emigration rush, the ageing process of the Romanian population has become increasingly serious, argued by a rate of 19.4% over 60-year-old population, of which 24.5% (2008) belongs to the rural area. The main responsible reason for this demographic and social situation is the replacement of the traditional reproduction pattern, mainly characterized by high birth and death rates, with a modern one, characterized by very low rates of the same kind. Low values in natality were, on one hand, the result of a steady regression of fertility, and on the other of, a drop in general mortality, hence the lengthening of the average life-span. To be able to cope with a relatively new phenomenon such as ageing of population, Romania needs to seriously consider adequate measures and steps towards achieving balance. Visionary strategy and plans require, well-grounded medium-and-long-term development programmes especially for the Romanian rural area.